Sludge dewatering method for activating persulfate through cooperation of hydrodynamic cavitation and electrochemical oxidation

By adding persulfate to the sludge and combining hydrocavitation and electrochemical oxidation treatment, the existing sludge dewatering methods are solved, and the efficient and low-energy-consuming sludge dewatering effect is achieved.

CN119912134AActive Publication Date: 2025-05-02HU-NAN NEW FRONTIER SCI & TECH LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510157107.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-05-02
Estimated Expiration
2045-02-13

AI Technical Summary

Technical Problem

The existing sludge dewatering methods have problems such as low dehydration efficiency, large energy consumption and insufficient moisture content after treatment, making it difficult to effectively treat sludge with high moisture content.

Method used

The sludge dehydration method of hydrocavitation and electrochemical oxidation activated persulfate is adopted. By adding persulfate to the sludge, hydrocavitation and electrochemical oxidation are carried out, the microbial cell wall is destroyed by electrochemical oxidation, and the extracellular polymer is destroyed by electrochemical oxidation, and the activate persulfate produces sulfate radicals to further decompose the sludge.

Benefits of technology

It improves the dehydration performance and efficiency of sludge, reduces energy consumption and chemical usage, and achieves efficient sludge dehydration, which is suitable for engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912134A_ABST
    Figure CN119912134A_ABST
Patent Text Reader

Abstract

The invention discloses a sludge dewatering method for activating persulfate through cooperation of hydrodynamic cavitation and electrochemical oxidation, which comprises the following steps: adding persulfate into sludge to be treated to obtain sludge containing persulfate, and carrying out hydrodynamic cavitation treatment on the sludge containing persulfate to obtain hydrodynamic cavitation treated sludge, according to the treatment method provided by the invention, the persulfate is firstly added into the sludge, and then the hydrodynamic cavitation treatment and the electrochemical oxidation treatment are performed in sequence, so that the dewatering performance of the sludge is improved, and the sludge can be recycled. Meanwhile, persulfate is activated, and the activated persulfate can generate sulfate free radicals with strong oxidizing property to decompose extracellular polymeric substances in the sludge, so that cell lysis and dehydration are further promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sludge treatment, and in particular to a sludge dehydration method using hydrodynamic cavitation in coordination with electrochemical oxidation to activate persulfate. Background Art

[0002] With the rapid development of my country's economy, the rapid improvement of urbanization and industrialization, the discharge of urban sewage and industrial wastewater has increased rapidly, and the output of sludge has increased year by year with the substantial increase in sewage treatment. Sludge has a high water content (up to 99.9%) and a large volume. It contains a large amount of bacteria, heavy metals, organic matter and other substances that are harmful to the environment. If it is not properly treated, it will cause great harm to the environment.

[0003] At present, the traditional sludge dewatering methods include natural drying, thermal drying and mechanical dewatering. However, these methods have more or less the disadvantages of low dehydration efficiency and high energy consumption, and the moisture content after treatment still cannot meet the requirements of sludge disposal, and deep dehydration is still required.

[0004] At present, the emerging sludge dewatering methods include ultrasound, hydraulic cavitation and electrochemical methods. Ultrasound produces sound waves to break the cells of sludge; hydraulic cavitation technology destroys the cell walls of microorganisms through the high temperature and high pressure environment generated by the collapse and bursting of bubbles, improves the dewatering performance and biodegradability of sludge, reduces the amount of sludge produced, and realizes the resource utilization of sludge; electrochemical oxidation dehydration is a relatively green sludge dehydration technology, which produces strong oxidizing substances to destroy the extracellular polymers in the sludge, promote cell lysis and thus promote dehydration, but hydraulic cavitation devices have the disadvantages of insignificant cavitation effect and low cavitation efficiency; the core of electrochemical sludge treatment is the electrode, but during the electrochemical oxidation process, active oxygen will be generated and adsorbed near the anode plate, so the degree of extracellular polymers and cell lysis is not high enough, and the dehydration effect is general. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a sludge dewatering method using hydrodynamic cavitation in conjunction with electrochemical oxidation to activate persulfate. The method provided by the present invention has simple process, high reaction efficiency, low dosage of reagents, low energy consumption, good dewatering performance, and is easy to apply in engineering.

[0006] In order to achieve the above purpose, the present invention adopts the following technical solutions

[0007] The invention provides a sludge dehydration method for persulfate activated by hydrodynamic cavitation synergistically with electrochemical oxidation. Persulfate is added to the sludge to be treated to obtain sludge containing persulfate, the sludge containing persulfate is subjected to hydrodynamic cavitation treatment to obtain hydrodynamic cavitation treated sludge, the hydrodynamic cavitation treated sludge is subjected to electrochemical oxidation treatment to obtain electrochemically oxidized sludge, and the electrochemically oxidized sludge is subjected to oxidation treatment to obtain the obtained sludge.

[0008] The treatment method provided by the present invention first adds persulfate to the sludge, and then performs a hydrodynamic cavitation treatment on the sludge. The hydrodynamic cavitation technology uses a high temperature and high pressure environment to open the chemical bonds between molecules, thereby destroying the cell walls of microorganisms, which can not only degrade the macromolecules in the sludge, but also generate a large number of hydroxyl free radicals to oxidize the chemical substances in the sludge, thereby improving the dehydration performance of the sludge. Subsequently, an electrochemical oxidation treatment is performed. The electrochemical oxidation generates hydroxyl free radicals with strong oxidizing properties, which can destroy the extracellular polymers in the sludge, promote cell lysis, and improve the dehydration performance of the sludge. At the same time, during the hydrodynamic cavitation and electrochemical oxidation processes, an activation effect is generated on the persulfate, and the activated persulfate can generate sulfate free radicals with strong oxidizing properties to decompose the extracellular polymers in the sludge, thereby further promoting cell lysis and dehydration.

[0009] In a preferred embodiment, the amount of persulfate added is 1-2 mmol / g VSS. When the amount of persulfate added is controlled within this range, the dehydration effect is optimal.

[0010] In a preferred embodiment, during the hydrodynamic cavitation treatment, the pressure is 1-5 bar and the reaction time is 5-10 min.

[0011] In actual operation, the sludge containing persulfate is added to the hydraulic cavitation system and the booster pump is turned on for treatment.

[0012] The preferred solution is that the electrochemical oxidation process is to insert electrodes into the activated sludge, set the plate spacing to 1-5 cm, turn on the power, and 2 Electrolysis was performed for 30-60 min at the current density.

[0013] Further preferably, the electrode cathode is selected from one of a titanium electrode, a copper electrode and an iron electrode, preferably a titanium electrode, and the anode is a boron-doped diamond electrode.

[0014] Further preferably, the substrate in the boron-doped diamond electrode is selected from one of polycrystalline silicon, single crystal silicon, and a composite substrate, preferably a composite substrate; the composite substrate consists of a silicon carbide / titanium composite layer located in the middle and boron-doped silicon carbide layers located on both sides.

[0015] When the boron-doped diamond electrode adopts a composite substrate, the electrochemical oxidation effect is optimal, so that the final sludge dehydration rate is the highest. The silicon carbide / titanium composite layer has a low thermal expansion coefficient and excellent conductivity. The boron-doped silicon carbide layers on both sides have a lower thermal expansion coefficient than the silicon carbide / titanium composite layer and have a certain conductivity, which matches the thermal expansion coefficient of diamond; at the same time, it has excellent corrosion resistance. The two work together to improve the conductivity of the substrate as a whole, reduce the thermal expansion coefficient, and avoid the diamond coating from peeling off from the substrate due to the large difference in thermal expansion coefficient when the diamond coating grows at high temperature; and silicon carbide and diamond can form a covalent bond (Si-C bond), which has a strong bonding force and makes the composite substrate and the diamond coating have high adhesion, and at the same time has excellent conductivity and strong corrosion resistance.

[0016] More preferably, in the composite substrate, the thickness of the silicon carbide / titanium composite layer is 0.5-5 mm, and the thickness of the boron-doped silicon carbide layer is 0.1-1 mm.

[0017] More preferably, in the silicon carbide / titanium composite layer, the volume fraction of silicon carbide is 70-98%, preferably 80-90%, and the volume fraction of titanium is 2%-30%, preferably 10-20%.

[0018] When the volume fraction of silicon carbide and titanium is controlled within the above range, the performance is optimal. If the volume fraction of titanium is too large, the overall thermal expansion coefficient of the substrate will increase, which is not conducive to the combination of the substrate and the diamond coating. If the volume fraction of metal is too small, the overall conductivity of the substrate will decrease, resulting in an increase in the resistivity of the overall material and increased energy consumption.

[0019] More preferably, in the boron-doped silicon carbide layer, the concentration of boron in the boron-doped silicon carbide layer is 1×10 18 -1×10 20 atoms / cm³.

[0020] In the present invention, the concentration of the doping element in the boron-doped silicon carbide layer is controlled within the above range, and the performance of the final obtained material is optimal. However, too high or too low a doping concentration will lead to a decrease in the conductivity of the doped non-metallic inorganic material.

[0021] Further preferably, when the substrate in the boron-doped diamond electrode is a composite substrate, the preparation process is: silicon carbide powder and titanium powder are mixed to obtain composite powder, three layers of powder, namely boron-doped silicon carbide powder, composite powder, and boron-doped silicon carbide, are laid in sequence in a mold, and then sintered to obtain a composite substrate, the composite substrate is surface pretreated, and then a doped diamond coating is grown on the surface of the composite substrate by chemical vapor deposition.

[0022] Further preferably, the sintering is SPS sintering, the SPS sintering temperature is 1000-1900°C, the holding time is 10-300min, the heating rate is 80-200°C / min, the pressure is 10-60Mpa, and the pulse duty cycle is 50%-90%. Through SPS spark plasma sintering, rapid densification technology can be achieved, grain growth can be effectively controlled, and the mechanical properties of the material can be improved.

[0023] More preferably, the process of surface pretreatment of the composite substrate is: firstly grinding the surface of the composite substrate, then performing sandblasting, and finally placing the sandblasted composite substrate in a diamond nanocrystal suspension for seed crystal planting.

[0024] In the present invention, the composite substrate is firstly ground to remove the oxide layer, reduce the roughness and make the surface flat, and then the surface micro-roughness is increased by sandblasting to provide more nucleation sites; the surface area is increased to improve the adhesion ability of the seed crystal; surface micro-pits are generated, which are beneficial to the mechanical bite of the seed crystal. In the present invention, grinding provides a good surface foundation for sandblasting, and sandblasting creates an ideal microstructure for seed crystal planting, and then cooperates with the seed crystal planting, and finally grows a high-quality doped diamond coating through the cooperation of the above-mentioned surface pretreatment means.

[0025] If only grinding is performed without sandblasting, the following will result: the surface is too smooth and lacks micro-roughness; the seed crystals are difficult to adhere to and fix on the substrate surface; there are insufficient nucleation sites, affecting the subsequent growth quality of the diamond film; if only sandblasting is performed without grinding, the original impurities and oxide layer on the surface cannot be completely removed; the sandblasting effect is uneven, resulting in inconsistent surface treatment; there may be large protrusions and defects on the substrate surface, affecting the uniformity of subsequent film growth.

[0026] More preferably, during the grinding, the grinding speed is controlled to be 15-30 rpm and the grinding time is 5-20 min.

[0027] More preferably, during the sandblasting treatment, the pressure is controlled to be 0.1-0.3 MPa, the time is 5-60 s, and the distance is 10-30 cm.

[0028] More preferably, the diamond nanocrystal suspension is obtained by dispersing nanodiamonds in pure water, and the particle size of the nanodiamonds is 1-25 nm.

[0029] More preferably, the seed crystal planting is carried out under ultrasound, and the ultrasound time is 30-60 minutes.

[0030] Further preferably, the process of chemical vapor deposition growth of boron-doped diamond coating is: placing the surface pretreated composite substrate in a chemical deposition furnace, the mass flow ratio of the introduced gas is hydrogen: methane: borane = 100-120: 2-10: 0.05-3, the growth pressure is 1-4Kpa, the growth temperature is 650-1000°C, the growth number is 2-4 times, each time the composite substrate is replaced with the front and back, and then the growth is continued, and the single growth time is 10-40h.

[0031] In a preferred embodiment, the oxidation treatment is carried out under stirring at a speed of 100-200 rpm and the oxidation treatment time is 1-2 hours. The activated persulfate is further oxidized and finally the sludge is dehydrated.

[0032] Principles and advantages

[0033] The treatment provided by the present invention first adds persulfate to the sludge, and then performs a hydrodynamic cavitation treatment on the sludge. The hydrodynamic cavitation technology uses a high temperature and high pressure environment to open the chemical bonds between molecules, thereby destroying the cell walls of microorganisms, which can not only degrade the macromolecules in the sludge, but also generate a large number of hydroxyl free radicals to oxidize the chemical substances in the sludge, thereby improving the dehydration performance of the sludge. Subsequently, an electrochemical oxidation treatment is performed. The electrochemical oxidation generates hydroxyl free radicals with strong oxidizing properties, which can destroy the extracellular polymers in the sludge, promote cell lysis, and improve the dehydration performance of the sludge. At the same time, during the hydrodynamic cavitation and electrochemical oxidation process, an activation effect is generated on the persulfate, and the activated persulfate can generate sulfate free radicals with strong oxidizing properties to decompose the extracellular polymers in the sludge, thereby further promoting cell lysis and dehydration.

[0034] In the electrochemical oxidation process, when the anode used is a boron-doped diamond electrode with a composite substrate, the silicon carbide / titanium composite layer in the composite substrate has a low thermal expansion coefficient and excellent electrical conductivity, and the boron-doped silicon carbide layers on both sides have a lower thermal expansion coefficient than the silicon carbide / titanium composite layer and a certain electrical conductivity, which matches the thermal expansion coefficient of diamond; at the same time, it has excellent corrosion resistance, and the conductivity of the substrate is improved by the synergy of the two, and the thermal expansion coefficient is reduced, so that the diamond coating is prevented from peeling off from the substrate due to the large difference in thermal expansion coefficient when the diamond coating grows at high temperature; and silicon carbide and diamond can form a covalent bond (Si-C bond), which has a strong bonding force and makes the composite substrate and the diamond coating have high adhesion, and at the same time has excellent electrical conductivity and strong corrosion resistance, so that the efficiency of electrochemical oxidation can be greatly improved, and the effect of persulfate activation is improved, so as to improve the final dehydration efficiency.

[0035] Compared with the prior art, the present invention has at least the following advantages:

[0036] 1. At the same time, hydraulic cavitation, electrochemical oxidation, persulfate oxidation and other technologies are used to break the sludge wall and dehydrate it, with high dehydration efficiency;

[0037] 2. Hydraulic cavitation can destroy the cell walls of microorganisms in sludge, and electrochemical oxidation can destroy extracellular polymers in sludge. The two can synergistically promote cell lysis and dehydration, and increase reaction efficiency;

[0038] 3. Hydrodynamic cavitation and electrochemical oxidation synergistically activate persulfate. The activated persulfate produces sulfate free radicals to further decompose the sludge after hydrodynamic cavitation and electrochemical oxidation treatment. The synergistic effect of the three promotes cell lysis and dehydration;

[0039] 4. The process is simple, the reaction efficiency is high, the amount of reagents used is small, the energy consumption is low, the dehydration performance is good, and it is easy to apply in engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A sludge dewatering process flow chart of hydrodynamic cavitation synergistically with electrochemical oxidation to activate persulfate. DETAILED DESCRIPTION

[0041] Example 1

[0042] Take 1L of municipal sludge with a moisture content of 98%, add 1.5mmol / g VSS of sodium persulfate, stir and dissolve, put it into the hydrodynamic cavitation device, turn on the booster pump, adjust the pressure to 3bar, react for 5min, and then insert electrode plates into the sludge, where the cathode is a titanium electrode and the anode is a boron-doped diamond electrode (the substrate is polycrystalline silicon), the plate spacing is 2cm, and the current density is set to 550A / m 2 , turn on the power, turn off the power after reacting for 40 minutes, stir at 100rpm for 1 hour, and after the reaction is completed, the sludge moisture content is measured to be 48.3%.

[0043] Comparative Example 1

[0044] Take 1L of municipal sludge with a moisture content of 98%, do not add persulfate, stir and dissolve it, then put it into the hydrodynamic cavitation device, turn on the booster pump, adjust the pressure to 3 bar, react for 5 minutes, and then insert electrode plates into the sludge, where the cathode is a titanium electrode and the anode is a boron-doped diamond electrode (the substrate is polycrystalline silicon). The distance between the plates is 2cm and the current density is set to 550A / m 2 , turn on the power, turn off the power after reacting for 40 minutes, stir at 100rpm for 1 hour, and after the reaction is completed, the sludge moisture content is measured to be 58.2%.

[0045] Example 2

[0046] Take 1L of municipal sludge with a moisture content of 99%, add 2mmol / g of sodium persulfate VSS, stir and dissolve it, put it into the hydrodynamic cavitation device, turn on the booster pump, adjust the pressure to 5bar, react for 10min, and then insert electrode plates into the sludge, where the cathode is a titanium electrode and the anode is a boron-doped diamond electrode (the substrate is polycrystalline silicon). The distance between the plates is 2cm and the current density is set to 800A / m 2 , turn on the power, turn off the power after reacting for 60 minutes, stir at 100rpm for 1 hour, and after the reaction is completed, the sludge moisture content is measured to be 40.5%.

[0047] Comparative Example 2

[0048] Take 1L of municipal sludge with a moisture content of 99%, add 2mmol / g of sodium persulfate VSS, stir and dissolve, and insert electrode plates into the sludge, where the cathode is a titanium electrode and the anode is a boron-doped diamond electrode (with a polycrystalline silicon substrate). The distance between the plates is 2cm and the current density is set to 800A / m 2 , turn on the power, turn off the power after reacting for 60 minutes, stir at 100rpm for 1 hour, and after the reaction is completed, the sludge moisture content is measured to be 72.6%.

[0049] Example 3

[0050] Take 1L of municipal sludge with a moisture content of 99%, add 1mmol / g VSS of sodium persulfate, stir and dissolve, put it into the hydrodynamic cavitation device, turn on the booster pump, adjust the pressure to 2bar, react for 8min, and then insert electrode plates into the sludge, where the cathode is a titanium electrode and the anode is a boron-doped diamond electrode (the substrate is polycrystalline silicon), the plate spacing is 2cm, and the current density is set to 300A / m 2 , turn on the power, turn off the power after reacting for 30 minutes, stir at 100rpm for 1 hour, and after the reaction is completed, the sludge moisture content is measured to be 53.8%.

[0051] Comparative Example 3

[0052] Take 1L of municipal sludge with a moisture content of 99%, add 1mmol / g VSS of sodium persulfate, stir to dissolve, and put it into the hydraulic cavitation device, turn on the booster pump, adjust the pressure to 2bar, react for 8min, and then stir at 100rpm for 1h. After the reaction is completed, the moisture content of the sludge is measured to be 68.3%.

[0053] Example 4

[0054] 1. Preparation of boron-doped silicon carbide powder:

[0055] The boron doping amount is 1×10 20atoms / cm³, high-purity SiC powder (purity ≥99.9%), B4C powder (purity ≥99.9%), and sintering aids Al2O3 and Y2O3 are mixed by ball milling at a speed of 800rpm for 24 hours to obtain a mixed powder, wherein the mass fraction of the sintering aid Al2O3 in the mixed powder is 0.5%, and the mass fraction of Y2O3 in the mixed powder is 0.5%. Then, under the protection of argon, the temperature is first increased to 1000℃ at a heating rate of 15℃ / min and kept for 1 hour, and then increased to 1800℃ and kept for 2h to obtain.

[0056] 2. Preparation of composite substrate:

[0057] Silicon carbide powder (80 vol%) and titanium powder (20 vol%) were mixed and ball-milled in a ball mill at 1200 rpm for 36 h to obtain a mixed powder; boron-doped silicon carbide powder, mixed powder, and boron-doped silicon carbide powder were laid in a mold in sequence, with the doping layer thickness of 0.5 mm and the intermediate composite layer thickness of 3 mm; SPS sintering was adopted with a temperature of 1550°C, a holding time of 120 min, a heating rate of 150°C / min, a pressure of 40 MPa, and a pulse duty cycle of 80%.

[0058] 3. Preparation of boron-doped diamond electrodes

[0059] The sintered sandwich structure composite substrate was surface treated by grinding at 20rpm for 15min, sandblasting (pressure 0.2MPa, time 30s, distance 20cm), and then seeding in 10nm diamond suspension (4g / L) by ultrasonic 45min; hot wire chemical vapor deposition (HFCVD) was used to grow doped diamond, gas flow ratio (H2:CH4:B2H6) = 110:5:2, pressure 2KPa, temperature 800℃, growth 3 times, each time 30h, and positive and negative replacement after each growth. A composite substrate with a resistivity of 0.2mΩ·cm was prepared. The resistivity of existing single crystal silicon is 2 mΩ·cm, which is 10 times lower than that of existing single crystal silicon substrates.

[0060] 4. Sludge dewatering

[0061] Take 1L of municipal sludge with a moisture content of 98%, add 1.5mmol / g VSS of sodium persulfate, stir and dissolve, put it into the hydrodynamic cavitation device, turn on the booster pump, adjust the pressure to 3bar, react for 5min, and then insert electrode plates into the sludge, where the cathode is a titanium electrode and the anode is a boron-doped diamond electrode. The distance between the plates is 2cm, and the current density is set to 550A / m 2 , turn on the power, turn off the power after reacting for 40 minutes, stir at 100rpm for 1 hour, and after the reaction is completed, the sludge moisture content is measured to be 41.1%.

Claims

1. A method for dewatering sludge by hydrodynamic cavitation combined with electrochemical oxidation to activate persulfate, characterized in that: Persulfate is added to the sludge to be treated to obtain sludge containing persulfate, the sludge containing persulfate is subjected to hydraulic cavitation treatment to obtain hydraulic cavitation treated sludge, the hydraulic cavitation treated sludge is subjected to electrochemical oxidation treatment to obtain electrochemical oxidation treated sludge, and the electrochemical oxidation treated sludge is subjected to oxidation treatment to obtain the obtained product.

2. The method for dewatering sludge by hydrodynamic cavitation combined with electrochemical oxidation and activation of persulfate according to claim 1, characterized in that: The added amount of the persulfate is 1-2 mmol / g VSS.

3. The method for dewatering sludge by hydrodynamic cavitation combined with electrochemical oxidation and activation of persulfate according to claim 1, characterized in that: During the hydrodynamic cavitation treatment, the pressure is 1-5 bar and the reaction time is 5-10 min.

4. A sludge dewatering method using hydrodynamic cavitation in conjunction with electrochemical oxidation activation of persulfate according to claim 1 or 2, characterized in that: The electrochemical oxidation process is as follows: insert the electrodes into the activated sludge, set the plate spacing to 1-5 cm, turn on the power, and 2 Electrolysis was performed for 30-60 min at the current density.

5. The method for dewatering sludge by hydrodynamic cavitation combined with electrochemical oxidation and activation of persulfate according to claim 4, characterized in that: The cathode of the electrode is selected from one of a titanium electrode, a copper electrode and an iron electrode, and the anode is a boron-doped diamond electrode; The substrate of the boron-doped diamond electrode is selected from polycrystalline silicon, single crystal silicon and a composite substrate.

6. The method for dewatering sludge by hydrodynamic cavitation combined with electrochemical oxidation and activation of persulfate according to claim 5, characterized in that: The substrate in the boron-doped diamond electrode is a composite substrate; the composite substrate is composed of a silicon carbide / titanium composite layer located in the middle and boron-doped silicon carbide layers located on both sides; In the composite substrate, the thickness of the silicon carbide / titanium composite layer is 0.5-5 mm, and the thickness of the boron-doped silicon carbide layer is 0.1-1 mm; In the silicon carbide / titanium composite layer, the volume fraction of silicon carbide is 70-98%, and the volume fraction of titanium is 2%-30%; In the boron-doped silicon carbide layer, the concentration of boron in the boron-doped silicon carbide layer is 1×10 18 -1×10 20 atoms / cm³.

7. The method for dewatering sludge by hydrodynamic cavitation combined with electrochemical oxidation and activation of persulfate according to claim 6, characterized in that: When the substrate in the boron-doped diamond electrode is a composite substrate, the preparation process is as follows: silicon carbide powder and titanium powder are mixed to obtain composite powder, three layers of powder, namely, boron-doped silicon carbide powder, composite powder, and boron-doped silicon carbide, are laid in a mold in sequence, and then sintered to obtain a composite substrate, the composite substrate is subjected to surface pretreatment, and then a doped diamond coating is grown on the surface of the composite substrate by chemical vapor deposition; The sintering is SPS sintering, the SPS sintering temperature is 1000-1900°C, the holding time is 10-300min, the heating rate is 80-200°C / min, the pressure is 10-60Mpa, and the pulse duty cycle is 50%-90%.

8. The method for dewatering sludge by hydrodynamic cavitation combined with electrochemical oxidation and activation of persulfate according to claim 7, characterized in that: The process of surface pretreatment of the composite substrate is: firstly grinding the surface of the composite substrate, then sandblasting, and finally placing the sandblasted composite substrate in a diamond nanocrystal suspension for seed crystal planting; During the grinding, the grinding speed is controlled to be 15-30 rpm and the grinding time is 5-20 min; During the sandblasting treatment, the pressure is controlled to be 0.1-0.3 MPa, the time is 5-60 s, and the distance is 10-30 cm; The diamond nanocrystal suspension is obtained by dispersing nanodiamonds in pure water, and the particle size of the nanodiamonds is 1-25 nm; The seed crystal planting is carried out under ultrasound, and the ultrasound time is 30-60 minutes.

9. The method for dewatering sludge by hydrodynamic cavitation combined with electrochemical oxidation and activation of persulfate according to claim 7, characterized in that: The process of chemical vapor deposition growth of boron-doped diamond coating is as follows: placing a composite substrate with a surface pretreatment in a chemical deposition furnace, introducing gas at a mass flow ratio of hydrogen: methane: borane = 100-120: 2-10: 0.05-3, a growth pressure of 1-4 KPa, a growth temperature of 650-1000°C, and a growth number of 2-4 times. Each time the composite substrate is grown, the front and back sides are replaced, and the growth is continued. The single growth time is 10-40 hours.

10. A sludge dewatering method using hydrodynamic cavitation in conjunction with electrochemical oxidation to activate persulfate according to claim 1 or 2, characterized in that: The oxidation treatment is carried out under stirring, the stirring speed is 100-200 rpm, and the oxidation treatment time is 1-2 hours.

Citation Information

Patent Citations

  • Pretreatment method for strengthening dehydration of drilling sludge under combined action of ultrasonic wave and sulfate radical anion oxidation

    CN106746440A

  • Ultrasonic coupling photoelectric Fenton activated persulfate water treatment system and water treatment method

    CN111646634A

  • Method for dewatering excess sludge by electrocatalytic coupling sulfate radical free radicals

    CN111977939A

  • Method for improving dewatering performance of dredging sediment through BDD anode electro-activation persulfate

    CN115417475A

  • Water medium treatment method and apparatus using ultrasonic treatment and diamond electrode

    JP2008093569A